Nivel de conocimiento sobre alimentación cariogénica y no cariogénica dirigida a los padres de los niños menores de 5 años de la parroquia rural Manú, del cantón Saraguro, provincia de Loja, periodo octubre 2021-marzo 2022 - Aldeán Pinzón, Luis Eduardo (2022)
We define a cariogenic diet as the intake of foods with a high content of carbohydrates, especially sugars which easily deposit on the retentive tooth surfaces. Therefore, this increases the risk of producing caries since there is a general lack of knowledge about the influence of nutrition in the first years of life and the prevention of the disease at later ages, which generates great interest in the importance of nutrition in critical stages of development. The following descriptive crosssectional study aims to determine the level of knowledge of parents of children under five years of age in the rural parish of Manú about cariogenic and noncariogenic food through the application of a survey in person and individually addressed to 146 representatives, which consisted of 8 multiple choice questions about knowledge, type of food, quantity, and frequency of consumption. We observed that the representatives surveyed are at a medium level of knowledge. With 61.0% on cariogenic and non-cariogenic food. After having carried out the research project and through the values obtained, we can indicate that the level of knowledge presented by parents about cariogenic and noncariogenic feeding is in a medium range; therefore, it is of vital importance to carry out the constant intervention in this population, thus allowing their knowledge and lifestyle to improve, allowing future research to show significant changes